Equilíbrio trabalho-família no modelo home-office - Almeida, Nathalia dos Santos Batista (Universidade Federal de São Carlos, 2019)
The entrance of woman in the working Market from the 1960s forged discussions about the balance between work and family. The hegemonic family structure of this time had at its core a heterosexual couple, in which the man occupied the role of provider and the woman caregiver .Almost 70 years later, this family structure is still the most common in Brazil, however, these roles are more diffuse. The sphere of work has also changed. New models emerged and began to affect intrafamily relationships. Home-office work is an example of new work models, which emerged approximately in the 1970s and are tending to increase. Few Brazilian studies have investigated the impacts of this model on family balance, so this study aims to investigate whether there is a difference in the workplace and the division of household and family tasks, perception of emotional support, job satisfaction, quality of life and self esteem. The study included 27 women and 7 men working in a centralized environment and 28 women and 6 men who worked from home, aged between 18 and 56 years. Participants were recruited from social medias and answered an online questionnaire consisting of characterization questions, Critério Brasil, Quality of Life Scale, Self-Esteem Scale, Work Satisfaction Scale and Task Division Scale. Data were statistically analyzed from measures of central tendency and dispersion and correlation data between variables. The results indicated that there were no statistically significant differences between centralized local workers and those who use from their homes in relation to the analyzed variation; a workday and task-related quality of life for the centralized workgroup rather than the home-office group. It was concluded that the balance factors between work and family are the same for both work models.
Work-family balance in home-office model
Keywords: Família nuclear.; equilíbrio trabalho-família; home-office; Nuclear family; work-family balance; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO TRABALHO E ORGANIZACIONAL::FATORES HUMANOS NO TRABALHO